Pengaruh Variasi Kekasaran Lubang Nozzle Dengan Campuran Bahan Bakar Pertalite dan Spiritus Terhadap Karakteristik Nyala Api - Muhammad Firmansyah; Ikhwanul Qiram; Gatut Rubiono (Virtual of Mechanical Engineering Article, 2021)
The nozzle is a fluid flow spraying device to increase the velocity of the outflow. Differences in the nozzle holes can affect the flow of fluid that comes out. The purpose of the study was to determine the effect of variations in nozzle hole roughness with a mixture of pertalite and spiritus fuels on the characteristics of the flame. In this research, experimentally using Nozzle Cutting Tip LPG M.02 with a given treatment of threading roughness in the nozzle hole with a thread spacing of 0.5mm, 1mm, and without treatment (Standard) while the fuel used is a mixture of Pertalite and Pertalite fuels. spirit with a mixture of (75ml:75ml), (100ml:50ml), and (125ml:25ml), data collection includes the rate of fuel consumption for 3 minutes, the temperature of the fire includes (bottom, middle, top fire) with a distance of each measurement 20cm, height fire, cross-sectional area of fire and area based on the color of the fire which is then to determine the characteristics of the fire produced in each variation used. The results showed that the treatment of roughness of threading at the nozzle hole and the mixing of fuel between Pertalite and Spiritus had an effect on the characteristics of the flame, where the highest change in fire characteristics was in the variation of the 1mm threaded nozzle hole with the percentage of the fuel mixture 125ml:25ml with an air flow pressure of 0.5 LPM. . It has a fuel consumption rate of 9 ml/minute, fire temperature (below 776 oC, middle 717 oC, above 617oC), flame height is 73.21cm, and blue flame area is 31.22cm2.Keywords: Nozzle, Pertalite, Spiritus, Fire Characteristics